Preliminary assessment of sea level rise impacts to coastal ecosystems in Thua Thien - Hue - Tuan, Le Xuan (VNU Journal of Science: Earth and Environmental Sciences; Vol 28 No 2, 2012)
Abstract. Coastal ecosystems such as estuaries, lagoons, gulfs, mangroves, coral reefs, sea grasses support high productivity and biodiversity in Viet Nam. The coastal ecosystems play a crucial role not only in biodiversity reserve but also in socio-economic and local residents’ daily life. In the setting of increasing affection of climate change, researching impacts of sea level rise to the coastal ecosystems is necessary. This paper provide picture of coastal ecosystems and assessment of sea level rise impacts on the ecosystems in Thua Thien – Hue. In this study, climate change vulnerability is applied as methodology for the assessment. The focused factors caused by sea level rise include inundation, flood, erosion, wetland loss, and increased salt water intrusion.   The analyses show that, sea level rise has different impact on communities in the coastal areas in Thua Thien Hue. Among them, seagrass communities in the lagoons seem to be more vulnerable compared to the others. Keywords: sea level rise, coastal ecosystems, vulnerability, adaptation, lagoons